Chemotherapy-induced testicular toxicity - Allen, Caroline Margaret (The University of Edinburgh, 2021)
Childhood cancer survival rates have continued to increase in recent decades, with current survival rates of around 80%. This is due in large part to improvements in cancer treatment including the use of chemotherapy drugs. Chemotherapy treatment during childhood can adversely affect the reproductive system, resulting in infertility in adulthood. Gonadotoxicity and associated infertility risk of chemotherapy agents used to treat childhood cancer is, however, debated and often based on adult patients. Clinically, there are no fertility preservation options available for prepubertal boys since, unlike adult men, they do not yet produce mature spermatozoa for routine sperm cryopreservation. Alternatively, cytoprotective agents could be given alongside the cancer treatment to mitigate chemotherapy-induced damage to healthy reproductive tissues, without interfering with the ability to treat the cancer. In order to develop cytoprotective agents, a thorough understanding of the underlying mechanism of action and molecular targets of chemotherapy agents are required, specifically in relation to the prepubertal testis. In this thesis, two models of the prepubertal testis were used to study chemotherapy-induced testicular toxicity, a mouse prepubertal testis tissue culture model and a rat GC-6spg cell line model, representative of spermatogonial stem cells. Firstly, the gonadotoxicity of first- and second-generation drugs of the platinum alkylating-like drug class were compared, to determine whether the newer generation drug carboplatin was less gonadotoxic than cisplatin, as reported for other organ specific toxicities. This proved not to be the case, with carboplatin found to be equally gonadotoxic to the prepubertal testis as cisplatin, reducing the density of proliferating germ cells. Given these results, there is no indication that modifying treatment regimens to include carboplatin instead of cisplatin would spare the testis from chemotherapy-induced testicular toxicity. The role of reactive oxygen species (ROS) and oxidative stress in chemotherapy-induced damage, as well as the protective effects of antioxidants, against cisplatin-, doxorubicin- or vincristine-induced gonadotoxicity were also examined. Cisplatin and doxorubicin are known to be gonadotoxic, with the general underlying mechanisms of action linked to oxidative stress. In contrast, vincristine has not been considered to be gonadotoxic based on adult fertility rates, and has also not been thought to induce oxidative stress as a mechanism of action. The results from both models, however, indicate that vincristine is gonadotoxic to the prepubertal testis, causing accumulation of germ cells into the centre of seminiferous tubules in the prepubertal testis model. Preliminary data could not rule out a role for ROS and oxidative stress in chemotherapy-induced damage: further work is required to optimize the techniques for assessment of ROS and oxidative stress. Co-treatment with antioxidants melatonin, n-acetylcysteine (NAC) and lycopene produced differing results depending on the chemotherapy drug. High concentrations of melatonin and NAC partially protected against cisplatin-induced damage, whereas NAC enhanced vincristine cytotoxicity and lycopene treatment alone was cytotoxic to the GC-6spg cell line. Overall, these results are a step towards furthering our understanding of the underlying mechanism of toxicity of commonly used chemotherapy agents in the prepubertal testis. Drugs that are currently considered less gonadotoxic, often from limited clinical information, should be investigated for their direct effects on the prepubertal testis since this may differ from the adult testis. In addition, antioxidants may be beneficial or detrimental in protecting the testis from chemotherapy-induced testicular toxicity.
Keywords: chemotherapy drug damage; gonadotoxicity; carboplatin; cisplatin; gonadotoxic; vincristine; oxidative stress